Phosphate removal from wastewater for the manufacture of struvite fertilizer - Dyah Suci Perwitasari,; Nur Aini Fauziyah,; Pardi Sampe Tola,; Stefanus Muryanto,; Jamari Jamari,; Athanasius Priharyoto Bayuseno, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
One of the non-renewable natural resources is phosphate rock. Phosphate is currently a lot necessity, while the need for phosphate is estimated to last within 30 to 300 years. Therefore, it is necessary to strive for the development of new sustainable sources of phosphate to maintain phosphate stability. Stirring is an efficient method in the crystallization process where the stirring speed affects the growth of struvite crystals. The purpose of this study was to study the growth of struvite crystals with the struvite crystallization process with the influence of stirring rotations of 100, 150 and 200 rpm at a temperature of 30oC. The experiment was carried out by mixing the two solutions in a 1000 ml glass beaker. The reaction time and pH of struvite crystallization were evaluated in this experiment. The crystals obtained were characterized using a scanning electron microscope (SEM) with energy dispersion x-ray (EDX) and x-ray fluorescence (XRF). From the results of the study, it was found that the highest P2O5 content at a stirring speed of 100 rpm and a temperature of 30oC was 47.5%, and was included in the quality of triple superphosphate fertilizer.The morphology of the irregular flake crystals was a typical form of struvite crystals with a size of 20 m.